Approaches in the Treatment of Complex Shoulder Instability - Vinall, Phil (MD Conference Express, 2014)
Michel Latarjet was the first physician to treat recurrent anterior instability of the shoulder with coracoid transfer and attachment of the conjoined tendon to the anterior glenoid with screws. The procedure, which carries his name, was first performed in 1954 and remains in use today for extra-articular treatment of anterior glenohumeral joint instability. This article discusses recent studies on the use of the Laterjet procedure, arthroscopic approaches for the Latarjet procedure, appropriate use of the Hill-Sachs remplissage procedure, as well as shoulder arthrodesis.